Penicilina y Bencilpenicilina (1997)
ABSTRACT: Among antibacterial agents the Betalactamic groups in today one of the main of antibiotics in infections therapy, this set the beginning of antibacterials new wave of pharmacological substance. From Betalactamics, Penicillin and Benzilpnicillin are the most widely used in humans and animals. In food animals, these are use for mammary, respiratory and genitourinary treatment and occasionally as well as food aditives to prevent disease and as feed efficiency enhancer.